Prophylaxis of caries with fluoride for children under five years - Sophie Jullien (BMC, 2021)
Abstract We looked at existing recommendations and supporting evidence on the effectiveness and potential harms of the different fluoride interventions in preventing dental caries in children under 5 years of age. We conducted a literature search up to the 12th of September 2019 by using key terms and manual search in selected sources. We summarized the recommendations and the strength of the recommendation when and as reported by the authors. We summarized the main findings of systematic reviews with the certainty of the evidence as reported. Water fluoridation has been widely implemented worldwide for several decades and evidence shows it reduces the prevalence of dental caries. Salt or milk fluoridation are other collective fluoride interventions that are also effective to prevent dental caries in children. The evidence of effects of oral fluoride supplements for caries prevention is limited and inconsistent. The use of fluoride toothpastes has consistently been proven to be effective in the prevention of dental caries. The evidence for the effects of the different levels of fluoride concentration in toothpastes is more limited. Topical fluorides (gels and varnishes) are effective in preventing dental caries and are mainly recommended to children with high risk of dental caries. Early childhood intake of fluoride supplements and fluoride level of 0.7 ppm (ppm) in drinking water are associated with the risk of dental fluorosis, ranging from minor forms to severe forms that are of aesthetic concerns.